Assessment of student-teachers' digital competencies across educational aspects: the current status and areas for improvement (Educational Dimension, 2025)
In the present digital age, improved teacher digital competencies are increasingly becoming an important component of teachers' qualifications. The purpose of this study was to investigate the digital competencies level of student-teachers and probe the areas for improvement. The subject of this study was undergraduate student-teachers in their final year of Bachelor of Education degree programmes from the College of Education at one of the public Universities in Tanzania. Purposive and convenience sampling techniques were employed to get a sample of 549 participants. The study employed the UNESCO ICT Competency Framework for Teachers (ICT CFT) as a theoretical framework. The study employed a quantitative approach and descriptive cross-sectional design. Data were collected through an online survey that included six competency areas linked to teachers' professional practices. Data analysis procedures included descriptive and inferential analysis. The findings revealed that student-teachers perceived their digital competencies as moderately higher at the knowledge acquisition level and moderately low at the knowledge deepening level of ICT CFT. The results also demonstrated that student-teachers were more competent in integrating technology in educational aspects that are indirectly linked to teaching (e.g. teacher professional learning, and organization and administration) and less competent in educational aspects that are directly linked to classroom teaching (e.g. pedagogy, and curriculum and assessment). The study further established a positive and statistically significant association between student-teachers' digital competencies and knowledge acquisition and knowledge deepening levels. The results of the present study signify the importance of developing student-teachers' digital competencies across all educational aspects. However, in order to guarantee technology integration in classroom teaching, it is recommended that teacher education programmes focus more on improving student-teachers' digital competencies in competency areas that are directly linked to classroom pedagogical practices.
Keywords: digital competence; digital transformation; ICT CFT; teacher digital competence; student-teachers; technology integration